PEMANFAATAN BLOTONG DAN PUPUK SINTETIK DALAM MEMPERBAIKI SIFAT KIMIA ULTISOL DAN PERTUMBUHAN BIBIT KELAPA SAWIT - Ika Ayu Putri Septyani; Syafrimen Yasin; Gusmini Gusmini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Most of the oil palm cultivation in Ultisols who have low fertility, nutrient deficiency and toxicity of micronutrient. The objectives of this research were to explore the interaction between sugarcane filter-cake (blotong) compost with synthetic fertilizer to improving chemical properties of Ultisols, growth of oil palm seedling, and the benefit of compost to save on the use of synthetic fertilizer. This research used a completely randomized factorial design, with two factors and three replication. The first factor was level of compost (0, 0.5, 0.75 kg polybag-1). The second factor was level of synthetic fertilizer (0, 0.25, 0.5, 0.75, 1 recommendation). The result showed that addition of compost till 0.75 kg/polybag in Ultisols could improve chemical properties of Ultisols like pH 6.11 units, organic C by 4.27%, total N by 0.47%, exchangeable-Ca by 7.78 cmolckg-1, exchangeable-Mg by 1.01 cmolckg-1, exchangeable-K by 0.36 cmolckg-1, CEC by 31.94 cmolc.kg-1 and decreased exchangeable-Al till not measurable. Combination of compost and synthetic fertilizer gave the interaction to increasing growth of oil palm seedling and nutrient uptake like tall of stem by 65.17 cm, biomass by 46.38 g, nutrient uptake of N by 62.47g crop-1. From this research recommended addition 0.5 kg polybag-1 compost and 0.5 R synthetic fertilizer to decrease the used of synthetic fertilizer till 50%, so that support soil health and environment.